Synthesis and characterization of 4-(((3-mercapto-5-phenyl-4H-1,2,4-triazole-4-yl)imino)methyl)-2-methoxyphenol and its complexes with Zr(IV), Cd(II) and Sn(II) ions - I. Al-Abdali, Basim; A. Ali, Atheer (Iraqi Journal of Science, 2023)
A series of coordination compounds of Zr(IV), Cd(II) and Sn(II) ions with 4-(((3-mercapto-5-phenyl-4H-1,2,4-triazole-4-yl)imino)methyl)-2-methoxyphenol, as a ligand has been successfully prepared in alcoholic medium. The prepared complexes were characterized quantitatively and qualitatively by using: elemental analysis CHNS, FT-IR spectroscopy, UV-visible spectroscopy, 1H and 13CNMR, atomic absorption measurements, magnetic susceptibility, thermal analysis)TG and DTG) and conductivity measurements. This ligand coordinates as a bidentate that to the metal ions through sulphur and nitrogen of (azomethine group) atoms. According to the spectral data, Cd(II)- and Sn(II)-complexes have coordination of 6 with octahedral geometry while the Zr(IV)-complex has coordination of 7 with exhibited a pentagonal bipyramid.